Additive manufacturing infill optimization for automotive 3D-printed ABS components. Issue 1 (15th August 2019) - Schmitt, Matt; Mehta, Raj Mattias; Kim, Il Yong
Abstract : Purpose: Lightweighting of components in the automotive industry is a prevailing trend influenced by both consumer demand and government regulations. As the viability of additively manufactured designs continues to increase, traditionally manufactured components are continually being replaced with 3D-printed parts. The purpose of this paper is to present experimental results and design considerations for 3D-printed acrylonitrile butadiene styrene (ABS) components with non-solid infill sections, addressing a large gap in the literature. Information published in this paper will guide engineers when designing fused deposition modeling (FDM) ABS parts with infill regions. Design/methodology/approach: Uniaxial tensile tests and three-point bend tests were performed on 12 different build configurations of 20 samples. FDM with ABS was used as the manufacturing method for the samples. Failure strength and elastic modulus were normalized on print time and specimen mass to quantify variance between configurations. Optimal infill configurations were selected and used in two automotive case study examples. Findings: Results obtained from the uniaxial tensile tests and three-point bend tests distinctly showed that component strength is highly influenced by the infill choice selected. Normalized results indicate that solid, double dense and triangular infill, all with eight contour layers, are optimal configurations for component regions experiencing high stress, moderate stress and low stress, respectively. Implementation of the optimal infill configurations in automotive examples yielded equivalent failure strength without normalization and significantly improved failure strength on a print time and mass normalized index. Originality/value: To the best of the authors' knowledge, this is the first paper to experimentally determine and quantify optimal infill configurations for FDM ABS printed parts. Published data in this paper are also of value to engineers requiring quantitative material properties for common infill configurations.